2015
DOI: 10.1155/2016/8548910
|View full text |Cite
|
Sign up to set email alerts
|

An Abnormal Nitric Oxide Metabolism Contributes to Brain Oxidative Stress in the Mouse Model for the Fragile X Syndrome, a Possible Role in Intellectual Disability

Abstract: Background. Fragile X syndrome is the most common genetic cause of mental disability. Although many research has been performed, the mechanism underlying the pathogenesis is unclear and needs further investigation. Oxidative stress played major roles in the syndrome. The aim was to investigate the nitric oxide metabolism, protein nitration level, the expression of NOS isoforms, and furthermore the activation of the nuclear factor NF-κB-p65 subunit in different brain areas on the fragile X mouse model. Methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 45 publications
(42 reference statements)
0
10
0
1
Order By: Relevance
“…Reduced BDNF levels in the brain has been studied in the context of downstream result of deregulated NO synthesis, and also resulting cognitive impairment (Canossa et al, 2002;Banoujaafar et al, 2016). In the cortex and the hippocampus, NO shows gradual decline with aging (Reckelhoff et al, 1994;Lima-Cabello et al, 2016). Clinical samples of blood plasma in aged individuals have been studied to show higher levels of NO and has been implicated to loss of auditory-verbal as well as visual-spatial based working memory along with impairment of short term declarative memory (Talarowska et al, 2012).…”
Section: Changes At the Epigenetic Levelmentioning
confidence: 99%
“…Reduced BDNF levels in the brain has been studied in the context of downstream result of deregulated NO synthesis, and also resulting cognitive impairment (Canossa et al, 2002;Banoujaafar et al, 2016). In the cortex and the hippocampus, NO shows gradual decline with aging (Reckelhoff et al, 1994;Lima-Cabello et al, 2016). Clinical samples of blood plasma in aged individuals have been studied to show higher levels of NO and has been implicated to loss of auditory-verbal as well as visual-spatial based working memory along with impairment of short term declarative memory (Talarowska et al, 2012).…”
Section: Changes At the Epigenetic Levelmentioning
confidence: 99%
“…However, it remains unexplored whether mitochondrial dysfunction contributes to pathogenesis of FXS. A limited number of studies have shown metabolic changes in the brain of Fmr1 KO mice, including increased rate of glucose metabolism 18 , elevated metabolic and oxidative stress 19 , increased ROS production, and abnormal nitric oxide metabolism 20, 21 , as well as altered energy metabolism at the systemic level 22 . FMRP promotes protein translation of Superoxide Dismutase, a regulator of oxidative stress 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Contribution of altered DNA repair to onset of IDs has been suggested through identification of causative mutations in several DNA repair genes 16 , 17 . Besides increase in the mutation frequency and altered DNA repair, the hypersensitivity to oxidative stress might be particularly relevant for the onset of HUWE1-promoted XLID, as enhanced oxidative stress and insufficient antioxidant defense were suggested to play important pathophysiological role in XLID 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Mutation frequency was highest in the HUWE1 p.R4187C XLID cells and was accompanied with a decreased DNA repair capacity and hypersensitivity to oxidative stress. While accumulation of de novo mutations was previously shown to negatively affect functioning of developmental genes 23 , increased oxidative stress was suggested to have particular pathophysiological role in neurodevelopmental disorders, including XLID 24 , 25 . Immunoblot analysis of HUWE1 targets showed an XLID-specific down-regulation of oxidative stress response enzyme Polλ that was caused by the hyperactive HUWE1 p.R4187C.…”
Section: Introductionmentioning
confidence: 99%